Selenium-doped iron oxyhydroxide and a method for producing the same
Patent Information
- Application Number
- CN202311614285.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-11-29
AI Technical Summary
目前,大多数研究都是通过多步合成方法制备铁硒化合物,这样通过繁琐的制备方法所得到的硒化铁材料性能不佳且稳定性较差
[0018] (1) This invention innovatively develops a unique one-step electrodeposition method, in which selenium, a non-metallic element, is doped during the growth of iron hydroxyl oxide to form a selenium-doped iron hydroxyl oxide. This material exhibits a unique nanoflower structure, and the preparation process is simple and easy to operate. The selenium-doped iron hydroxyl oxide grows on a conductive substrate, forming a nanoflower-like structure composed of thin nanosheets, which can fully expose the active sites. At the same time, the doping of selenium is beneficial to enhancing the conductivity of iron hydroxyl oxide and improving the electron transfer ability, thereby promoting the reaction kinetics of the oxygen evolution reaction and ultimately significantly improving the seawater oxidation performance of the electrode.
Smart Images

Figure CN117626345B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of seawater decomposition oxygen production catalyst technology, and particularly relates to a selenium-doped iron hydroxyl oxide and its preparation method. Background Technology
[0002] With the increasing depletion of non-renewable energy sources such as fossil fuels, the efficient development of green energy is becoming increasingly urgent. Compared with traditional non-renewable energy sources, hydrogen energy (H2) has many advantages, including being green and pollution-free, having high energy density, abundant reserves, wide application range, and being recyclable. Among them, electrocatalytic water splitting, as an economical and green method of hydrogen production, can effectively solve major problems such as the energy crisis and environmental pollution. In recent years, people have been committed to preparing efficient and stable water electrolysis catalysts through simple and easy-to-operate processes to bridge the gap between basic research and industrial applications of water electrolysis. Currently, there are three types of electrolyzers commonly used in low-temperature water electrolysis for hydrogen production: alkaline electrolyzers (ALK), proton exchange membrane electrolyzers (PEM), and anion exchange membrane electrolyzers (AEM). These three types of electrolyzers have all achieved water electrolysis reactions at high current densities required by industry to varying degrees. However, considering the problem of water shortage caused by the continuous electrolysis of freshwater resources, more attention has been paid to the electrolysis of seawater. Seawater is abundant, contains a large number of ions, and is itself conductive. However, seawater electrolysis also presents many challenges: during the process of seawater electrolysis, the anode undergoes a competitive reaction of oxygen evolution (OER) and chlorine evolution (CER), which requires our electrode to have an overpotential of less than 480mV and good resistance to chloride ion corrosion.
[0003] Therefore, designing efficient, stable, and inexpensive non-precious metal electrocatalysts to achieve efficient seawater electrolysis is particularly important. It is well known that catalysts composed of precious metals (Pt / C, IrO2, and RuO2) possess excellent catalytic performance. However, due to the high cost and limited reserves of precious metals on Earth, the development of non-precious metal electrocatalysts is still hoped for to achieve large-scale, efficient seawater electrolysis. Among these, two-dimensional transition metal chalcogenides (TMDs) with their unique graphene-like structures have attracted widespread attention. Among chalcogenides, Se has a larger atomic radius, stronger metallicity, and lower ionization energy than S, making selenides in the TMD family a promising alternative to precious metal-based catalysts in water electrolysis. Simultaneously, iron-based transition metal catalysts readily form the intrinsically active substance FeOOH, which oxidizes water, during the OER process, further reducing the reaction overpotential. Currently, most studies prepare iron selenide compounds through multi-step synthesis methods. However, the iron selenide materials obtained through these cumbersome preparation methods exhibit poor performance and instability. Summary of the Invention
[0004] The purpose of this invention is to provide a selenium-doped iron hydroxyl oxide and its preparation method, thereby addressing the problems mentioned in the background section.
[0005] The present invention is implemented as follows: a selenium-doped iron hydroxyl oxide nanoflower structure is grown in situ on a conductive substrate by a one-step electrodeposition method, wherein the iron atom content is 30.26% to 79.63% and the selenium atom content is 0.28% to 1.57%.
[0006] The nanoflowers are composed of stacked thin nanosheets of different sizes, with the planar dimensions of the nanosheets being 30-150 nm in width and 100-700 nm in length.
[0007] Another objective of this invention is to provide a method for preparing selenium-doped iron hydroxyl oxide, comprising the following steps:
[0008] Step 1: First, add iron salt, selenium dioxide, calcium salt and lithium salt to deionized water and stir to form a mixed solution;
[0009] Step 2: Place the conductive substrate in the above mixed solution as the working electrode, perform electrodeposition at a constant voltage, rinse it clean after the reaction is complete, and dry it in an oven to obtain selenium-doped iron hydroxy oxide nanoflowers grown on the conductive substrate.
[0010] In a further technical solution, the conductive substrate is any one of the following conductive materials: nickel foam, nickel mesh, nickel felt, stainless steel felt, nickel-iron foam, copper foil, copper foam, iron foam, titanium mesh, carbon cloth, carbon paper, graphite felt, carbon fiber, and carbon materials obtained by calcining various fruit shells and mollusk shells.
[0011] In a further technical solution, the iron salt is any one of Fe(NO3)3, Fe2(SO4)3 and FeCl3, and the concentration range of the iron salt is 0.01 to 0.50 mol / L.
[0012] In a further technical solution, the concentration range of the selenium dioxide is 0.01 to 0.03 mol / L.
[0013] In a further technical solution, the constant voltage value is -1.8 to -1.0V.
[0014] In a further technical solution, the deposition time is 100–1200 s.
[0015] Another objective of this invention is to provide an application of selenium-doped iron hydroxyl oxide, specifically by applying the selenium-doped iron hydroxyl oxide nanoflower material to an oxidation reaction in alkaline water or alkaline seawater.
[0016] A further technical solution, the specific method of the application is as follows: placing selenium-doped iron hydroxyl oxide nanoflower material in an alkaline system as an oxygen evolution electrode for the oxidation reaction of alkaline water and alkaline seawater.
[0017] The present invention provides a selenium-doped iron hydroxyl oxide and its preparation method, the beneficial effects of which are as follows:
[0018] (1) This invention innovatively develops a unique one-step electrodeposition method, in which selenium, a non-metallic element, is doped during the growth of iron hydroxyl oxide to form a selenium-doped iron hydroxyl oxide. This material exhibits a unique nanoflower structure, and the preparation process is simple and easy to operate. The selenium-doped iron hydroxyl oxide grows on a conductive substrate, forming a nanoflower-like structure composed of thin nanosheets, which can fully expose the active sites. At the same time, the doping of selenium is beneficial to enhancing the conductivity of iron hydroxyl oxide and improving the electron transfer ability, thereby promoting the reaction kinetics of the oxygen evolution reaction and ultimately significantly improving the seawater oxidation performance of the electrode.
[0019] (2) The selenium-doped iron hydroxyl oxide nanoflowers provided by this invention, as oxidation electrodes for alkaline water and alkaline seawater, exhibit excellent catalytic activity and stability. At 10, 100, and 500 mA / cm², they showed good catalytic activity and stability. 2 At current densities of 192, 221, and 262 mV, the required overpotential in alkaline aqueous solutions is significantly lower than that of the control iron hydroxyl oxide nanosheets. Simultaneously, this catalyst exhibits excellent performance at 500 mA / cm² current densities. 2 The electrocatalytic decomposition of alkaline seawater solution at a constant current density can operate stably for over 550 hours without significant degradation in water oxidation performance. This performance is superior to most existing iron-based catalysts. Attached Figure Description
[0020] Figure 1 Images of selenium-doped iron hydroxyl oxide (Se-FeOOH) nanoflowers grown on a nickel foam substrate after electrodeposition at different magnifications using scanning electron microscopy (SEM).
[0021] Figure 2 Images of iron hydroxyl oxide (FeOOH) nanosheet arrays grown on nickel foam substrates after electrodeposition at different magnifications using scanning electron microscopy (SEM).
[0022] Figure 3 This is a distribution diagram of Fe, Se, and O elements in Se-FeOOH;
[0023] Figure 4(a) shows the X-ray diffraction (XRD) patterns of FeOOH and Se-FeOOH; (b) shows the Raman spectra of FeOOH and Se-FeOOH; (c) shows the Fe 2p energy level diagram of X-ray photoelectron spectroscopy (XPS) of FeOOH and Se-FeOOH; and (d) shows the Se 3d energy level diagram of Se-FeOOH via XPS.
[0024] Figure 5 The graph shows the OER performance of Se-FeOOH in alkaline aqueous electrolyte (1 mol / L potassium hydroxide) compared with other samples; (a) linear sweep voltammetry (LSV) curve; (b) comparison of overpotential at different current densities; (c) Tafel slope graph; (d) electrochemical impedance spectroscopy (EIS).
[0025] Figure 6 The graph shows the OER performance comparison of Se-FeOOH in alkaline seawater electrolyte (1 mol / L potassium hydroxide + seawater) with other samples; (a) LSV curve; (b) overpotential comparison at different current densities; and (c) performance curve of stable test at high current density. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0027] The specific implementation of the present invention will be described in detail below with reference to specific embodiments.
[0028] An embodiment of the present invention provides a selenium-doped iron hydroxyl oxide, wherein a selenium-doped iron hydroxyl oxide nanoflower structure is grown in situ on a conductive substrate by a one-step electrodeposition method, wherein the iron atom content is 30.26% to 79.63% and the selenium atom content is 0.28% to 1.57%.
[0029] In this embodiment of the invention, the nanoflower is composed of stacked thin nanosheets of different sizes, and the planar dimensions of the nanosheets are: width 30-150nm and length 100-700nm.
[0030] An embodiment of the present invention provides a method for preparing selenium-doped iron hydroxyl oxide, comprising the following steps:
[0031] Step 1: First, add iron salt, selenium dioxide, calcium salt and lithium salt to deionized water and stir to form a mixed solution;
[0032] Step 2: Place the conductive substrate in the above mixed solution as the working electrode, perform electrodeposition at a constant voltage, rinse it clean after the reaction is complete, and dry it in an oven to obtain selenium-doped iron hydroxy oxide nanoflowers grown on the conductive substrate.
[0033] In a preferred embodiment of the present invention, the conductive substrate includes any one of the following conductive materials: nickel foam, nickel mesh, nickel felt, stainless steel felt, nickel-iron foam, copper foil, copper foam, iron foam, titanium mesh, carbon cloth, carbon paper, graphite felt, carbon fiber, and carbon materials made from various fruit shells and mollusk shells after calcination.
[0034] In a preferred embodiment of the present invention, the iron salt is any one of Fe(NO3)3, Fe2(SO4)3 and FeCl3, and the concentration range of the iron salt is 0.01 to 0.50 mol / L.
[0035] In a preferred embodiment of the present invention, the concentration of selenium dioxide is in the range of 0.01 to 0.03 mol / L.
[0036] In a preferred embodiment of the present invention, the constant voltage value is -1.8 to -1.0V.
[0037] In a preferred embodiment of the present invention, the deposition time is 100-1200 s.
[0038] One embodiment of the present invention provides an application of selenium-doped iron hydroxyl oxide, wherein the selenium-doped iron hydroxyl oxide nanoflower material is applied to the oxidation reaction of alkaline water or alkaline seawater.
[0039] As a preferred embodiment of the present invention, the specific method of application is as follows: placing selenium-doped iron hydroxyl oxide nanoflower material in an alkaline system as an oxygen evolution electrode for oxidation reactions in alkaline water and alkaline seawater.
[0040] The following are several specific embodiments provided to verify the present invention:
[0041] Example 1: Step 1: First, place a 1cm*2cm piece of metallic nickel foam in a 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water in sequence for ultrasonic cleaning for 15 minutes, and then dry it for later use.
[0042] Step 2: Add 0.06 mol / L ferric chloride, 0.01 mol / L selenium dioxide, 0.20 mol / L lithium chloride and 0.03 mol / L calcium chloride to deionized water and stir for 30 minutes to form a mixed solution;
[0043] Step 3: Place the nickel foam in the above mixed solution and perform electrodeposition at a constant voltage of -1.4V for a constant time of 700s. After the reaction is completed, rinse it clean and then dry it in an oven set at 50℃ for 6 hours to obtain selenium-doped iron hydroxyl oxide nanoflower catalyst (denoted as "Se-FeOOH") grown in situ on nickel foam.
[0044] The application of selenium-doped iron hydroxyl oxide nanoflowers was also provided. The steps are as follows: Selenium-doped iron hydroxyl oxide nanoflowers were placed in a three-electrode system as the working electrode for oxygen evolution, a graphite rod was used as the counter electrode, and a mercury / mercury oxide electrode was used as the reference electrode. The alkaline electrolyte was 1 mol / L potassium hydroxide dissolved in deionized water, and the alkaline seawater electrolyte was 1 mol / L potassium hydroxide dissolved in seawater solution. The supernatant was taken, and the pH of the solution was 14. The alkaline water oxidation reaction performance was tested.
[0045] In this embodiment of the invention, the morphology of the prepared catalyst was observed on a JEOL JSM-7900 electron beam at an intensity of 12.6 keV. Figure 1 and Figure 2 It can be seen that Se-FeOOH exhibits a nanoflower structure formed by stacking different nanosheets, while FeOOH only shows a single nanosheet structure.
[0046] Depend on Figure 3 It can be seen that Fe, Se and O elements are uniformly distributed on the nanoflower structure, successfully proving the formation of FeOOH and the successful incorporation of Se into FeOOH.
[0047] Depend on Figure 4 (a) It can be seen that the characteristic peaks on the XRD pattern match those of Ni (PDF#4-850), indicating that the substrate material of the catalyst is a metallic nickel substrate; Figure 4 (b) shows a comparison of the Raman spectra of the two samples. It can be found that both samples have characteristic peaks belonging to FeOOH. After Se doping, the Se-FeOOH sample showed characteristic peaks of Fe-Se, indicating that Se was successfully incorporated. Figure 4 (c) shows a comparison of the Fe 2p energy level spectra of the XPS of the two samples, and the FeOOH catalyst. 3+ with Fe 2+ The peak area is 1.10:1. After Se doping, the Fe content of the Se-FeOOH catalyst is... 3+ with Fe 2+ The peak area ratio of 0.35:1 indicates that the Fe valence state has decreased. Figure 4 (d) shows the comparison of the Se 3d energy level spectra of this Se-FeOOH in XPS, which shows the presence of Se-O signal peaks.
[0048] Figure 5 (a) and (b) show the linear sweep voltammetry (LSV) curves of FeOOH, Se-FeOOH, and commercial IrO2 samples in 1 mol / L potassium hydroxide solution, as well as detailed comparisons of OER overpotentials. It can be seen that the introduction of Se significantly improves the OER performance of FeOOH, at 10, 100, and 500 mA / cm². 2 At current densities of [value missing], the required overpotentials in alkaline aqueous solutions are as low as 192, 221, and 262 mV, far superior to commercially available IrO2 samples. Further calculations of the Tafel slopes of these samples were performed as follows: Figure 5 As shown in (c), the Se-FeOOH sample exhibits a low Tafel slope of 22.95 mV / dec, indicating that Se doping promotes faster OER reaction kinetics. Simultaneously, Se modification also enhances the conductivity of FeOOH, thereby facilitating rapid electron transfer on the catalyst, as... Figure 5 (d) shows the smaller charge transfer resistance of Se-FeOOH on the electrochemical impedance spectroscopy.
[0049] Figure 6 (a) and (b) show the linear sweep voltammetry (LSV) curves of FeOOH and Se-FeOOH samples in alkaline seawater solution (1 mol / L potassium hydroxide + seawater), and a detailed comparison of OER overpotentials, respectively. Furthermore, as... Figure 6 (c) shows the stability test results, where the undoped FeOOH sample at 500 mA / cm²... 2 It can only operate for about 60 hours at a current density of 500 mA / cm², but the Se-FeOOH sample can operate at 500 mA / cm². 2 It can operate stably for 550 hours under a constant current density, and its seawater oxidation performance has not significantly decreased, which is far superior to the stability of the FeOOH sample.
[0050] Example 2: Step 1: First, place a 2cm*4cm copper foam in a 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water in sequence for ultrasonic cleaning for 15 minutes, and then dry it for later use.
[0051] Step 2: Then add 0.01 mol / L ferric nitrate, 0.01 mol / L selenium dioxide, 0.20 mol / L lithium chloride and 0.03 mol / L calcium chloride to deionized water and stir for 30 minutes to form a mixed solution;
[0052] Step 3: Place the copper foam in the above mixed solution and perform electrodeposition at a constant voltage of -1.8V for a constant time of 100s. After the reaction is completed, rinse it clean and then dry it in an oven set at 50℃ for 6 hours to obtain selenium-doped iron hydroxyl oxide nanoflower catalyst grown in situ on copper foam.
[0053] The application of selenium-doped iron hydroxyl oxide nanoflowers was also provided. The steps are as follows: Selenium-doped iron hydroxyl oxide nanoflowers were placed in a three-electrode system as the working electrode for oxygen evolution, a graphite rod as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode. A 3 mol / L potassium hydroxide solution was dissolved in deionized water as the alkaline electrolyte, and a 3 mol / L potassium hydroxide solution was dissolved in seawater as the alkaline seawater electrolyte. The supernatant was collected, and the solution pH was 14. The alkaline water oxidation performance was tested. The sample showed performance at 10, 100, and 500 mA / cm². 2 The overpotential of alkaline water / alkaline seawater oxidation at the given current density is shown in Table 1.
[0054] Example 3: Step 1: First, place a 3cm*5cm carbon cloth in a 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water in sequence for ultrasonic cleaning for 15 minutes, and then dry it for later use.
[0055] Step 2: Then add 0.25 mol / L ferric sulfate, 0.03 mol / L selenium dioxide, 0.20 mol / L lithium chloride and 0.03 mol / L calcium chloride to deionized water and stir for 30 minutes to form a mixed solution;
[0056] Step 3: Arrange carbon in the above mixed solution and perform electrodeposition at a constant voltage of -1.6V for a constant time of 300s. After the reaction is completed, rinse it clean and then dry it in an oven set at 50℃ for 6 hours to obtain selenium-doped iron hydroxyl oxide nanoflower catalyst grown in situ on carbon cloth.
[0057] The application of selenium-doped iron hydroxyl oxide nanoflowers was also provided. The steps are as follows: Selenium-doped iron hydroxyl oxide nanoflowers were placed in a three-electrode system as the working electrode for oxygen evolution, a graphite rod as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode. A 3 mol / L potassium hydroxide solution was dissolved in deionized water as the alkaline aqueous electrolyte, and a 5 mol / L potassium hydroxide solution was dissolved in seawater as the alkaline seawater electrolyte. The supernatant was collected, and the solution pH was 14. The alkaline water oxidation performance was tested. The sample showed performance at 10, 100, and 500 mA / cm². 2 The overpotential of alkaline water / alkaline seawater oxidation at the given current density is shown in Table 1.
[0058] Example 4: Step 1: First, place a 2cm*5cm piece of nickel-iron foam in 0.10mol / L hydrochloric acid solution, anhydrous ethanol and deionized water in sequence for ultrasonic cleaning for 5 minutes, and then dry it for later use.
[0059] Step 2: Then add 0.35 mol / L ferric chloride, 0.02 mol / L selenium dioxide, 0.2 mol / L lithium chloride and 0.03 mol / L calcium chloride to deionized water and stir for 30 minutes to form a mixed solution;
[0060] Step 3: Place the nickel-iron foam in the above mixed solution and perform electrodeposition at a constant voltage of -1.4V for a constant time of 500s. After the reaction is completed, rinse it clean and then dry it in an oven set at 50℃ for 6 hours to obtain selenium-doped iron hydroxyl oxide nanoflower catalyst grown in situ on nickel-iron foam.
[0061] The application of selenium-doped iron hydroxyl oxide nanoflowers was also provided. The steps are as follows: Selenium-doped iron hydroxyl oxide nanoflowers were placed in a three-electrode system as the working electrode for oxygen evolution, a graphite rod as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode. A 4 mol / L potassium hydroxide solution was dissolved in deionized water as the alkaline electrolyte, and a 6 mol / L potassium hydroxide solution was dissolved in seawater as the alkaline seawater electrolyte. The supernatant was collected, and the solution pH was 14. The alkaline water oxidation performance was tested. The sample showed performance at 10, 100, and 500 mA / cm². 2 The overpotential of alkaline water / alkaline seawater oxidation at the given current density is shown in Table 1.
[0062] Example 5: Step 1: First, place a 2cm*3cm piece of metallic nickel felt in a 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water in sequence for ultrasonic cleaning for 15 minutes, and then dry it for later use.
[0063] Step 2: Then add 0.45 mol / L ferric nitrate, 0.03 mol / L selenium dioxide, 0.2 mol / L lithium chloride and 0.03 mol / L calcium chloride to deionized water and stir for 30 minutes to form a mixed solution;
[0064] Step 3: The nickel felt is placed in the above mixed solution and electrodeposited at a constant voltage of -1.2V for a constant time of 900s. After the reaction is completed, it is rinsed clean and then dried in an oven set at 50℃ for 6 hours to obtain selenium-doped iron hydroxyl oxide nanoflower catalyst grown in situ on nickel felt.
[0065] The application of selenium-doped iron hydroxyl oxide nanoflowers was also provided. The steps are as follows: Selenium-doped iron hydroxyl oxide nanoflowers were placed in a three-electrode system as the working electrode for oxygen evolution, a graphite rod as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode. A 6 mol / L potassium hydroxide solution was dissolved in deionized water as the alkaline aqueous electrolyte, and a 4 mol / L potassium hydroxide solution was dissolved in seawater as the alkaline seawater electrolyte. The supernatant was collected, and the solution pH was 14. The alkaline water oxidation reaction performance was tested. The sample showed positive results at 10, 100, and 500 mA / cm². 2 The overpotential of alkaline water / alkaline seawater oxidation at the given current density is shown in Table 1.
[0066] Example 6: Step 1: First, place a 2cm*2cm stainless steel felt in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water in sequence for ultrasonic cleaning for 15 minutes, and then dry it for later use.
[0067] Step 2: Then add 0.50 mol / L ferric sulfate, 0.01 mol / L selenium dioxide, 0.20 mol / L lithium chloride and 0.03 mol / L calcium chloride to deionized water and stir for 30 minutes to form a mixed solution;
[0068] Step 3: Place the stainless steel felt in the above mixed solution and perform electrodeposition at a constant voltage of -1.0V and a constant time of 1200s. After the reaction is completed, rinse it clean and then dry it in an oven set at 50℃ for 6 hours to obtain selenium-doped iron hydroxyl oxide nanoflower catalyst grown in situ on stainless steel felt.
[0069] The application of selenium-doped iron hydroxyl oxide nanoflowers was also presented. The steps were as follows: Selenium-doped iron hydroxyl oxide nanoflowers were placed in a three-electrode system as the working electrode for oxygen evolution, a graphite rod as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode. A 6 mol / L potassium hydroxide solution was dissolved in deionized water as the alkaline electrolyte, and a 6 mol / L potassium hydroxide solution was dissolved in seawater as the alkaline seawater electrolyte. The supernatant was collected, and the solution pH was 14. The alkaline water oxidation performance was tested. The sample showed performance at 10, 100, and 500 mA / cm². 2 The overpotential of alkaline water / alkaline seawater oxidation at the given current density is shown in Table 1.
[0070] Table 1. Summary of alkaline seawater oxidation performance of Se-FeOOH samples prepared by different embodiments.
[0071]
[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing selenium-doped iron hydroxyl oxide, characterized in that, Selenium-doped iron hydroxyl oxide nanoflower structures were grown in situ on a conductive substrate using a one-step electrodeposition method, wherein the iron atom content ranged from 30.26% to 79.63% and the selenium atom content ranged from 0.28% to 1.57%. The nanoflowers are composed of stacked nanosheets of different sizes, and the planar dimensions of the nanosheets are: width 30-150 nm and length 100-700 nm. The preparation method includes the following steps: Step 1: First, add iron salt, selenium dioxide, calcium salt and lithium salt to deionized water and stir to form a mixed solution; Step 2: Place the conductive substrate in the mixed solution as the working electrode and perform electrodeposition at a constant voltage. After the reaction is complete, rinse it clean and dry it in an oven to obtain selenium-doped iron hydroxy oxide nanoflowers grown on the conductive substrate.
2. The method for preparing selenium-doped iron hydroxyl oxide according to claim 1, characterized in that, The conductive substrate is any one of the following: nickel foam, nickel mesh, nickel felt, stainless steel felt, nickel-iron foam, copper foil, copper foam, iron foam, titanium mesh, carbon cloth, carbon paper, graphite felt, and carbon fiber.
3. The method for preparing selenium-doped iron hydroxyl oxide according to claim 1, characterized in that, The iron salt is any one of Fe(NO3)3, Fe2(SO4)3 and FeCl3, and the concentration range of the iron salt is 0.01~0.50 mol / L.
4. The method for preparing selenium-doped iron hydroxyl oxide according to claim 1, characterized in that, The concentration range of the selenium dioxide is 0.01~0.03 mol / L.
5. The method for preparing selenium-doped iron hydroxyl oxide according to claim 1, characterized in that, The constant voltage value is -1.8 ~ -1.0 V.
6. The method for preparing selenium-doped iron hydroxyl oxide according to claim 1, characterized in that, The deposition time is 100~1200 s.
7. An application of selenium-doped iron hydroxyl oxide, based on the selenium-doped iron hydroxyl oxide prepared by the preparation method according to any one of claims 1-6, characterized in that, The selenium-doped iron hydroxyl oxide nanoflower material is applied to the oxidation reaction of alkaline water or alkaline seawater.
8. The application of selenium-doped iron hydroxyl oxide according to claim 7, characterized in that, The specific method of the application is as follows: selenium-doped iron hydroxyl oxide nanoflower material is placed in an alkaline system as an oxygen evolution electrode for the oxidation reaction of alkaline water and alkaline seawater.
Citation Information
Patent Citations
Full iron-based oxygen evolution catalyst as well as preparation method and application thereof
CN109999845A